Oxidation-induced negative Poisson's ratio of phosphorene. (11th July 2018) - Hao, Feng; Liao, Xiangbiao; Li, Mingjia; Xiao, Hang; Chen, Xi
Abstract: Mechanical properties of phosphorene oxides are investigated by using density functional theory calculations. Intriguingly, as the oxygen coverage approaches 50%, negative Poisson's ratios are found in the in-plane principal directions, originating from the asymmetric atomic structure upon oxygen adsorption. It is demonstrated that the structure of phosphorene oxide is largely weakened compared with that of pristine phosphorene. Our work indicates that certain unconventional mechanical properties, such as the negative Poisson's ratio, can be achieved by tuning the atomic structure through simple processes, which offers a new avenue to design specific properties at the nanoscale.